Cultures of America Japanese Americans - Lee, Lauren (Marshall Cavendish Corporation, 1996)
Provides a history of Japanese immigration to the United States and discusses Japanese customs and contributions to American culture.
Keywords: People & Places; General; Juvenile Nonfiction; United States